TIPE KEPRIBADIAN MELALUI MYERS BRIGGS TYPE INDICATOR DENGAN KINERJA PERAWAT DI RUANG RAWAT INAP RSUD TARAKAN - auliya, fida nabilah; Siregar, Tatiana (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
In maintaining and improving the quality of hospital services is determined by the quality of nurse performance. Nurse performance is influenced by several factors, one of which is psychological factors, namely personality between individuals. However, the results of psychological tests based on MBTI personality types with professional nurses are still rarely found. So his study aims to explore the MBTI trend towards professional nurses and determine the MBTI personality type with nurse performance results. The research design was quantitative with analytic descriptive method through comparative approach. Purposive sampling as many as 230 respondents as sampling. Analyzed with the Non Parametric Kruskall Wallis Test, and the results showed a p value of 0.198> 0.05 (Sig 95%) which means there is no significant difference between the MBTI personality type of nurses and the performance of nurses at RSUD Tarakan Jakarta. The results found that there were only 14 personality types and no ENTP and ENFP personality types were found in nurses at RSUD Tarakan. Based on the highest rank is the INTP personality type which increases the average nurse performance of 193.50 and the lowest rank is the INFJ personality type with an average performance of 65.75. This means that the nurse's MBTI personality type with nurse performance there is no real or significant difference between the performance of nurses at RSUD Tarakan Jakarta with 14 personality types, or in other words the results of the performance of nurses at RSUD Tarakan with 14 personality types can be said to be the same on the nurse's MBTI personality type in the inpatient room of RSUD Tarakan Jakarta.